KEMBALI KE FILOLOGI: FILOLOGI INDONESIA DAN TRADISI ORIENTALISME - . Sudibyo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
To current generation of experts on humanities studies the very idea of philology suggests something antiquarian and musty. In order to avoid the stigma, firstly, cartography of the oriental philological studies is needed. Secondly, the theorem that philology is identical to the text editing and textual criticism needs to be reconsidered. It was used by orientalists to exploit the needed information for mastery goals. Therefore, decolonization of research method must be done. Thirdly, in connection with postcolonial realm, philology must be cosmopolitan and secular. Philology must familiarize itself with interdisciplinary studies and be sensitive to the development of new humanities theories because in fact philology is the most basic tool of the interpretive humanities.